Let's judge a magazine by its cover; A textual analysis of the covers of Gadis - Handajani, Suzie (UI Scholars Hub, 2014)
In this article, I analyse the covers of Gadis, a magazine for Indonesian teenage girls, from 2009 to 2013. Using textual analysis, I examine these magazine covers as manifestations of local gender ideology amidst pressures from a globalized market. The models on the magazine covers are the embodiment of ideal teenagers and they reflect the magazine's personification of Indonesian adolescents. Images of the models in conjunction with the article titles displayed on the covers construct dominant themes surrounding the lives of female adolescents. In this article, I argue that the dominant gender ideology is perpetuated by the magazine; however, the embodiment of the ideology is shifting from the girly adolescent image to that of a more mature and sophisticated young woman.